Pengaruh Spiritualitas Kewirausahaan, Pemasaran Media Sosial dan Kompetensi Wirausaha terhadap Kinerja Usaha pada Umkm Kabupaten Bekasi - Junedi Junedi; Adibah Yahya (Syntax Idea)
The condition of the business world is that there are still practices that only want to gain profit without paying attention to moral and ethical aspects. This research is a quantitative research with primary data and secondary data, the sample used is 100 business actors to determine the effect of the variables forming the business performance. Methods of data collection using questionnaires and observations, then the results were tested using the Statistical Package for the Social Sciences (SPSS) through validity-reliability tests, classical assumption tests and multiple regression analysis. The results of the study show that the spiritual variables of entrepreneurship and entrepreneurial competence have a significant influence on the business performance of SME’s in Bekasi Regency, while the variables of social media marketing do not have a significant effect.